EMAS SEBAGAI INSTRUMEN INVESTASI YANG AMAN PADA SAAT INSTRUMEN INVESTASI KEUANGAN LAIN MENGALAMI PENINGKATAN RESIKO - Sholeh, Mohammad (Jurnal Akuntansi AKUNESA, 2014)
Investment analysis in the global crisis becomes very important. The purpose of this analysis is to know the risk and result of each investment instrument used. The results of this analysis investment can be do to each investment instruments such as stocks, derivatives, foreign exchange, ang a gold produce a low risks and results tend to favor to gold investment. Information from this analysis can be used as a reference for investors before making an investment decision. Gold investment show prospects a safe and profitable for several years ago. So, gold investment can be as an alternative investment in the middle of global crisis that is going on.Keyword: instrument investment, risk and return of investment, global crisis